An Assessment of Early Childhood Education School Infrastructure to Support the Wash Program in Indonesia - Koenarso, Dyah Ageng Pramesty; Aziza, Aspiya (THUFULA, 2022)
The purpose of this study was to explain an assessment of early childhood education schools infrastructure to support the WASH program in Indonesia. Quantitative research data collection methods were carried out in a survey with 186 samples in Banjarmasin. All early childhood education schools in Banjarmasin City have clean water and handwashing facilities with soap with water sources from the Municipal Waterworks (PDAM). Drinking water storage is in gallons and uses a dispenser processed through filtration. There is 5% of drinking water in schools in the category of less safe for consumption. Unsafe drinking water is indicated to come from water filtration that lacks maintenance and regular checks. The toilets owned by the school are shared toilets that are not used separately. The septic tank is not in accordance with Indonesian National Standard (SNI) 2398:2017. Most early childhood education schools have provided trash cans in the toilets. Each early childhood education school has a person in charge of toilet cleanliness and has a schedule for cleaning toilets. The handwashing station is located adjacent to the toilet and has a warning (in the form of a poster or banner) for washing hands after defecating. For the waste disposal used for washing hands, some are channeled into sewers, flowed under schools, flowed into septic tanks, and flowed into rivers.